Antioxidant Properties of Herbal Tea Prepared from Red Dragon Fruit Peel with The Addition of Ginger - Neni Trimedona; Rahzarni Rahzarni; Syuryani Syahrul; Yenni Muchrida; Irwan Roza (Politeknik Pertanian Negeri Payakumbuh, 2020)
The peel of red dragon fruit usually discarded. It is rich in polyphenol compounds that have antioxidant activity and health benefits. This research aimed to determine the antioxidant properties of herbal tea such as phenolic content, betacyanin content, and antioxidant activity. The herbal tea prepared with hot oven drying methods, where’s the fresh peel of red dragon fruit and ginger were cut to be small pieces and dried at 60oC, and ground into tea powder then mixed as treatments. Results showed that the addition of ginger has no significant effect on phenolic content, and betacyanin content decreased by the addition of ginger. The phenolic content of herbal tea (0% ginger) and the highest addition of ginger (12%) were 3.39±1.19 mg GAE/g and 3.59±1.43 mg GAE/g respectively. The betacyanin content were 124.63±1.61 mg/100 g (0% ginger) and 104.01±2.99 mg/100g (12% ginger). As the amount of ginger added increased, the percentage of inhibition of herbal tea decreased from 66.23%±2.67 to 61.19%±2.45%.